Does Donation After Cardiac Death Utilization Adversely Affect Hepatocellular Cancer Survival?. Issue 9 (September 2016) - Khorsandi, Shirin Elizabeth; Yip, Vincent S.; Cortes, Miriam; Jassem, Wayel; Quaglia, Alberto; O'Grady, John; Heneghan, Michael; Aluvihare, Varuna; Agarwal, Kosh; Menon, Krishna; Vilca-Melendez, Hector; Prachalias, Andreas; et al.
Abstract : Background: Hepatocellular cancer (HCC) is an established indication for liver transplantation. This group is often allocated a donor after cardiac death (DCD) liver as a solution for waiting times. There are concerns that this approach may oncologically disadvantage HCC recipients. The aim of this study was to determine whether DCD transplantation was associated with poorer cancer-related survival in HCC. Methods: Study population was from a single institute (2001-2014) with an HCC listing diagnosis. Variables related to recipient, tumor, and graft were analyzed to determine association with HCC death. Results: There were 347 recipients listed for HCC of which 91 received a DCD. Donor after cardiac death and donor after brain stem death (DBD) had equivalent 1-, 3-, and 5-year overall ( P = 0.115) and cancer-specific survival ( P = 0.7). On univariate analysis recipient age, sex, model for end stage liver disease, viral etiology had no bearing on the risk of HCC death. Neither did the graft variables of type (DCD vs DBD), donor age, steatosis, cold ischemic time, peak aspartate transaminase, day 5 bilirubin or international normalized ratio after transplant. Only tumor variables of alpha-fetoprotein, number, total diameter, microvascular invasion, and differentiation were predictors of HCC death. On multivariate analysis, predictors of HCC death remained tumor number ( P = 0.002), total diameter of tumor(s) ( P < 0.001), microvascular invasion ( P = 0.025), and poor differentiation ( P = 0.021). Conclusions: Donor liver quality in terms of graft type (DCD) has no influence on cancer related survival in transplant for HCC (hazards ratio, 1.143; 95% confidence interval, 0.528-2.423; P = 0.752). Abstract : Whether donation after cardiac death (DCD) oncologically disadvantages hepatocellular carcinoma (HCC) recipients is unknown. The authors describe a large series where DCD and donor after brain stem death recipients had equivalent overall and cancer-specific survival and where only tumor variables were predictors of HCC death.